English Premier League and English Football League academy managers` experiences of how psychosocial skills and characteristics are identified and developed in youth academy soccer players - Barraclough, J.; Grecic, D.; Harper, D. (Journal of Sports Sciences, 2024)
Psychological skills and characteristics (PSCs) are vital for player development, yet there is a lack of agreement on which are important and how they should be identified and developed in academy players, creating barriers to implementation into curricula. The key stakeholder with considerable insight into PSC development is the academy manager (AM). The aims of this study were (a) explore AMs` experiences of PSC identification and development, (b) identify challenges AMs feel affect development of PSCs. Nine AMs (i.e. Category 1; n = 3, Category 2; n = 3 and Category 3; n = 3) comprising an average coaching experience of 20.4 ± 7.4 years and time in the role of 5.2 years ±3.2 years participated in semi-structured interviews. Reflexive thematic analysis generated themes identified ideal PSC outcomes that AMs felt were important. AMs identified current practices within academies alongside challenges: transitions, need to upskill coaches, access to additional support from external partners and National Governing Bodies. There was consensus that PSCs are key drivers of progression and that embedding them into the pathway was critical to facilitating development. Academies should think carefully about design, implementation and evaluation of programmes to support player PSC development for success during and after soccer careers.